Analisis dalam Peningkatan Ekspor Minyak Kelapa Sawit ke India - Rahmawati, Reni (Journal of Economics and Management Scienties, 2025)
This research aims to examine how much influence international prices, rupiah depreciation, and Indonesian government regulations have on increasing palm oil exports to India. The data collection method is through surveys and distributing questionnaires, with a sample of 100 respondents. The analytical method used is multiple linear regression analysis using SPSS. The research results obtained based on the partial test (t test) showed a positive and significant influence between international prices on increasing exports. There is a positive and significant influence between the depreciation of the rupiah and the increase in exports. There is a positive and significant influence between Indonesian government regulations on increasing exports. There is a positive and significant influence between international prices, rupiah depreciation, and Indonesian government regulations on increasing exports. The percentage contribution of the independent variables international prices, rupiah depreciation, and Indonesian government regulations to the dependent variable of increasing exports is 0.811 or 81.1%. Meanwhile, the remaining 0.189 or 18.9% is influenced by other variables outside this research.